Enhanced performance of solution-processed broadband photodiodes by epitaxially blending MAPbBr3 quantum dots and ternary PbSxSe1−x quantum dots as the active layer. (21st November 2017) - Sulaman, Muhammad; Yang, Shengyi; Jiang, Yurong; Tang, Yi; Zou, Bingsuo
Abstract: Organic–inorganic hybrid photodetectors attract more and more interest, since they can combine the advantages of both organic and inorganic materials into one device, and broadband photodetectors are widely used in many scientific and industrial fields. In this work, we demonstrate the enhanced-performance solution-processed broadband photodiodes by epitaxially blending organo-lead halide perovskite (MAPbBr3 ) colloidal quantum dots (CQDs) with ternary PbSx Se1−x CQDs as the active layer. As a result, the interfacial features of the hetero-epitaxial nanocomposite MAPbBr3 :PbSx Se1−x enables the design and perception of functionalities that are not available for the single-phase constituents or layered devices. By combining the high electrical transport properties of MAPbBr3 QDs with the highly radiative efficiency of PbS0.4 Se0.6 QDs, the photodiodes ITO/ZnO/PbS0.4 Se0.6 :MAPbBr3 /Au exhibit a maximum photoresponsivity and specific detectivity of 21.48 A W −1 and 3.59 × 10 13 Jones, 22.16 A W −1 and 3.70 × 10 13 Jones at room temperature under 49.8 μ W cm −2 532 nm laser and 62 μ W cm −2 980 nm laser, respectively. This is higher than that of the layered photodiodes ITO/ZnO/PbS0.4 Se0.6 /MAPbBr3 /Au, pure perovskite (MAPbBr3 ) (or PbS0.4 Se0.6 ) QD-based photodiodes reported previously, and it is also better than the traditional inorganic semiconductor-based photodetectors. Our experimental results indicate that epitaxially-aligned nanocomposites (MAPbBr3 :PbSx Se1−x ) exhibit remarkable optoelectronic properties that are traceable to their atomic-scale crystalline coherence, and one can utilize the excellent photocarrier diffusion from PbSx Se1−x into the perovskite to enhance the device performance from the UV-visible to infrared region.